Lμp-spectra of pseudo-differential operators associated with the Bessel operator - Upadhyay S.K.; Shukla P. (My University, 2025)
In this paper, the characterizations of the Lμp-spectra of pseudo-differential operators associated with the Bessel operator are investigated by exploiting the theory of the Hankel transform for 1≤p<∞. Some applications related to the essential spectrum of pseudo-differential operators involving the Hankel transform in the Sobolev space, and in the heat equation are given. © 2021 Elsevier Masson SAS